TINDAK TUTUR DIREKTIF PEMBELAJARAN BAHASA INDONESIA DI SMPN 1 KENDAL TAHUN PELAJARAN 2023/2024 - Anggraini, Silvia Reni; Setyawati, Nanik; Ulumuddin, Arisul (Universitas Negeri Makassar, 2024)
This study aims to describe the form of directive speech acts in Indonesian language learning at SMP N 1 Kendal. This research is qualitative descriptive research. The research data were obtained from teachers‘ and students’ utterances in Indonesian language learning. The data sources of this research are Indonesian language teachers and students of class VIII. The data collection technique uses listening and note-taking techniques, while the data analysis technique uses agih and padan analysis methods. The technique of presenting data results using informal techniques. The results showed that there were 32 forms of directive speech acts in Indonesian language learning at SMPN 1 Kendal, including ordering, inviting, suggesting, requesting, and pleading. In this study, the data that often appears is the act of telling.